157k views
1 vote
Consider this rational equation.二+-==Use the least common denominator to simplify the rational equation into a standard form quadratic equation.Replace the values of b and to create the equation.

Consider this rational equation.二+-==Use the least common denominator to simplify-example-1
User Ayoub K
by
4.7k points

1 Answer

5 votes

ANSWER


\begin{equation*} x^2-10x+8=0 \end{equation*}

Step-by-step explanation

We want to rewrite the rational equation as a quadratic equation:


(1)/(x)+(1)/(x-2)=(1)/(4)

First, let us find the lowest common denominator for the left-hand side of the equation:


\begin{gathered} (1)/(x)+(1)/(x-2)=(1)/(4) \\ \\ (x-2+x)/(x(x-2))=(1)/(4) \\ \\ (2x-2)/(x^2-2x)=(1)/(4) \end{gathered}

Next, cross-multiply:


\begin{gathered} 4(2x-2)=x^2-2x \\ \\ 8x-8=x^2-2x \end{gathered}

Finally, move all the terms to the left-hand side and simplify:


\begin{gathered} 8x-8-x^2+2x=0 \\ \\ -x^2+2x+8x-8=0 \\ \\ -x^2+10x-8=0 \\ \\ \Rightarrow x^2-10x+8=0 \end{gathered}

That is the answer.

User Ahmed Ashour
by
5.1k points